Prognostic nutritional index as a potential predictor of prognosis in patients with sepsis: a retrospective cohort study - Pan, Mingyuan; Li, Zheng; Sheng, Shanfeng; Teng, Xiao; Li, Yuyang (Frontiers in Nutrition, 2025)
BackgroundSepsis patients often have immune dysfunction and malnutrition, which is a high-risk disease for death in critically ill patients. Although various biomarkers can predict the prognosis of sepsis patients, they are cumbersome to implement clinically. This study evaluates the prognostic potential of the Prognostic Nutritional Index (PNI) to fill this gap.MethodsWe conducted a retrospective analysis of data from patients admitted to the Intensive Care Unit (ICU) of Beth Israel Deaconess Medical Center with sepsis between 2008 and 2022. The Prognostic Nutritional Index (PNI) was calculated using the first measurement within 24 h of admission. Kaplan–Meier analysis was used to compare mortality risks among three groups, and a multivariable Cox proportional hazards regression model assessed the link between PNI and mortality risk in sepsis patients. Restricted cubic splines (RCS) explored the potential dose—response relationship between PNI and mortality, and threshold analysis determined the critical threshold of PNI. Receiver operating characteristic (ROC) analysis evaluated the predictive ability, sensitivity, and specificity of LAR for all—cause mortality in patients with liver cirrhosis and sepsis, and calculated the area under the curve (AUC). Finally, subgroup analyses were performed to evaluate the relationship between PNI and prognosis in different populations.ResultsA total of 6,234 patients were included Kaplan—Meier analysis showed that patients with high PNI had lower 14, 28, and 90-day all—cause mortality risks (all log—rank P < 0.001). The multivariable Cox proportional hazards model indicated that high PNI was independently associated with 14, 28, and 90-day all—cause mortality, with HRs of 0.62, 0.56, and 0.59 (all P < 0.0001), before and after adjusting for confounders RCS analysis revealed a non-linear link between PNI and short—and medium—term all—cause mortality in sepsis patients. A two—segment Cox proportional hazards model identified inflection points at 11.6 for 14-day, 11.2 for 28-day, and 11.2 for 90-day all-cause mortality ROC analysis showed PNI has lower predictive value for sepsis prognosis than sequential organ failure assessment and acute physiology and chronic health evaluation, yet it can enhance their predictive power Subgroup analyses found no significant interaction between PNI and specific subgroups.ConclusionThere is a significant association between short-term and medium—term all—cause mortality in sepsis patients and PNI, indicating that PNI can be a valuable indicator for predicting in—hospital and ICU mortality risk.